Effect of the variation in the extracellular concentration of l-arginine in the physiology of Leishmania (Viannia) braziliensis and its susceptibility to some antileishmanial drugs (2022)
ABSTRACT: The knowledge about amino acid metabolism in trypanosomatids is a valuable source of new therapeutic targets. l-arginine is an essential amino acid for Leishmania parasites, and it participates in the synthesis of polyamines, a group of essential nutrients used for nucleic acids, proteins biosynthesis, and redox modulation necessary for proliferation. In the present study, we evaluated the effect of changes in the availability of this amino acid on promastigotes and intracellular amastigotes on U937 macrophages and showed that the absence of l-arginine in culture medium negatively influences the growth and infectivity of Leishmania (Viannia) braziliensis, causing a decrease in the percentage of the infected cells and parasite load tested through light microscopy. In addition, the absence of l-arginine resulted in the parasite's inability to regulate its reactive oxygen species (ROS) production, which persisted for up to 24 h by flow cytometry following the probe H2DCF-DA dye. Moreover, the differentiation of promastigote to amastigote in axenic culture was more significant at low concentrations of l-arginine suggesting that this depletion induces a stress environment to increase this transformation under axenic conditions. No association was established between the availability of l-arginine and the effectiveness of antileishmanial drugs. All these results confirm the importance of l-arginine in L. braziliensis life cycle vital processes, such as its replication and infectivity, as documented in other Leishmania species. Based on these results, we proposed that the l-arginine uptake/metabolism route is possible in exploring new antileishmanial drugs.